1997
DOI: 10.1038/sj.ejcn.1600476
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and prevalence of obesity changes among Kuwaitis

Abstract: Objectives: To compare temporal changes in BMI, overweight (BMI b 25 kg/m 2 ) and obesity (BMI b 30 kg/ m 2 ) between two periods, among adult Kuwaitis. Design: Comparison of two independent cross-sectional samples of Kuwaitis studied in 1980±81 and 1993±94. Subjects: 2067 (896 men and 1171 women) and 3435 (1730 men and 1705 women) adult Kuwaitis (aged ! 18 y), drawn from primary health care (PHC) clinics and studied for nutritional assessment and for prevalence of obesity in 1980±81 and 1993±94, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…There have been several studies of single risk factors for chronic diseases in Kuwait, such as studies of overweight and obesity (Emara et al, 1989;Al-Isa, 1995, 1997a,b, 1999aAkanji et al, 1999;Al-Awadi & Amine, 1989;Malaviya et al, 1998;Moussa et al, 1999) or diabetes mellitus (Abdella et al, 1995(Abdella et al, , 1998(Abdella et al, , 1999. However, most of these studies have focused on children (Al-Isa, 1999a,b;Moussa et al, 1999), college students or other young adults (up to age 40 y) (AlIsa, 1995(AlIsa, , 1997a(AlIsa, ,b, 1999aAkanji et al, 1999;Al-Awadi & Amine, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies of single risk factors for chronic diseases in Kuwait, such as studies of overweight and obesity (Emara et al, 1989;Al-Isa, 1995, 1997a,b, 1999aAkanji et al, 1999;Al-Awadi & Amine, 1989;Malaviya et al, 1998;Moussa et al, 1999) or diabetes mellitus (Abdella et al, 1995(Abdella et al, , 1998(Abdella et al, , 1999. However, most of these studies have focused on children (Al-Isa, 1999a,b;Moussa et al, 1999), college students or other young adults (up to age 40 y) (AlIsa, 1995(AlIsa, , 1997a(AlIsa, ,b, 1999aAkanji et al, 1999;Al-Awadi & Amine, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The excluded articles included two review studies [16, 17], one letter to editor [39], one study with self-reported BMI [36], one study that reported body weight but not height [51], one study that focused on anthropometric measures other than BMI [41], and eleven studies [37, 38, 4247, 52–54] because of data overlap or redundancy. From among all studies with data overlap or redundancy, we selected the study reporting the most detailed results [19, 20, 2224, 33, 35]. The selection process resulted in a final total number of 18 articles remaining for a thorough review [1835] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…From among all studies with data overlap or redundancy, we selected the study reporting the most detailed results [19, 20, 2224, 33, 35]. The selection process resulted in a final total number of 18 articles remaining for a thorough review [1835] (Figure 2). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations